The faraway horses eaudiobook The adventures and wisdom of america's most renowned horsemen. - Brannaman, Buck (Tantor Media, 2011)
Nearly every week of the year, Buck Brannaman is on the road, conducting horsemanship clinics in which he teaches horse owners how to better understand and work with their animals, creating a relationship based on trust and respect rather than force. Buck's skill has become the stuff of legend—in fact, the main character in Robert Redford's film The Horse Whisperer was based largely on him, and he served as the director's technical adviser during the shoot. "These principles are really about life—about living your life so you're not at war with the horse, or with other people," Buck writes. At heart, this rich and rewarding autobiography is a prescription for living a harmonious existence—whether it involves horses or not.